Achieving exceptionally high strength in binary Mg-13Gd alloy by strong texture and substantial precipitates. (1st March 2021) - Li, R.G.; Li, H.R.; Pan, H.C.; Xie, D.S.; Zhang, J.H.; Fang, D.Q.; Dai, Y.Q.; Zhao, D.Y.; Zhang, H.
Abstract: Ultra-high strength is obtained in the simple binary Mg-Gd alloy with only a small extrusion ratio, and its main strengthening contribution is different from that reported in previous works. The tensile yield strength (TYS) of Mg-13Gd alloy can reach 350 MPa by hot extrusion with an extrusion ratio of 4. The strong texture and internal dislocation pinning of the un-dynamically recrystallized (un-DRXed) region with large proportion contribute greatly to the strength of as-extruded alloy. It is found for the first time that aging precipitation only occurs within the large un-DRXed grains but not in the fine DRXed grains. The TYS of extruded + peak-aged alloy increases to 470 MPa. The ultra-high strength is mainly related to texture strengthening and precipitation strengthening, rather than fine grain strengthening and precipitation strengthening in the conventional Mg alloys with large plastic deformation. Graphical abstract: High strength of 500 MPa is mainly attributed to the formation of strong texture and substantial prismatic β' precipitates distributed within the elongated grains. Almost no aging precipitation within the fine dynamical recrystallized grains is found for the first time. There is the Gd segregation at dislocation and the preferential nucleation of the prismatic β' precipitate along the dislocation line in the elongated grains of extruded sample. Image, graphical abstract